The relationship between kinematic determinants of jump and sprint performance in Division I women soccer players - McCurdy, K. W.; Walker, J. L.; Langford, G. A.; Kutz, M. R.; Guerrero, J. M.; McMillan, J. (The Journal of Strength and Conditioning Research, 2010)
The purpose of this study was to determine the relationship between measures of unilateral and bilateral jumping performance and 10- and 25-m sprint performance. Fifteen division I women soccer players (height 165 ± 2.44 cm, mass 61.65 ± 7.7 kg, age 20.19 ± 0.91 years) volunteered to participate in this study. The subjects completed a 10- and 25-m sprint test. The following jump kinematic variables were measured using accelerometry: sprint time, step length, step frequency, jump height and distance, contact time, concentric contact time, and flight time (Inform Sport Training Systems, Victoria, BC, Canada). The following jumps were completed in random order: bilateral countermovement vertical jump, bilateral countermovement horizontal jump, bilateral 40-cm drop vertical jump, bilateral 40-cm drop horizontal jump, unilateral countermovement vertical jump (UCV), unilateral countermovement horizontal jump, unilateral 20-cm drop vertical jump (UDV), and unilateral 20-cm drop horizontal jump (UDH). The trial with the best jump height or distance, reactive strength (jump height or distance/total contact time), and flight time to concentric contact time ratio (FT/CCT) was recorded to analyze the relationship between jump kinematics and sprint performance. None of the bilateral jump kinematics significantly correlated with 10- and 25-m sprint time, step length, or step frequency. Right-leg jump height (r = -0.71, p = 0.006, SEE = 0.152 seconds), FT/CCT (r = -0.58, p = 0.04, SEE = 0.176 seconds), and combined right and left-leg jump height (r = -0.61) were significantly correlated with the 25-m sprint time during the UCV. Right-leg FT/CCT was also significantly related to 25-m step length (r = 0.68, p = 0.03, SEE = 0.06 m) during the UDV. The combined right and left leg jump distance to standing height ratio during the UDH significantly correlated (r = -0.58) with 10-m sprint time. In comparison to bilateral jumps, unilateral jumps produced a stronger relationship with sprint performance.